Bioinspired Interface Design of Sewable, Weavable, and Washable Fiber Zinc Batteries for Wearable Power Textiles. (23rd August 2020) - Wang, Changfeng; He, Tao; Cheng, Jianli; Guan, Qun; Wang, Bin
Abstract: Wearable electronics have great demands for flexibility, high‐performance, and customized batteries that require the significant advancement of renewable and weavable power fiber design. Here, weavable, sewable, and washable aqueous zinc batteries (AZBs)‐based power fibers are developed by the synergistic interfacial design of the quinone‐rich polydopamine as organic redox‐active cathodes and nano‐binders on the carbon substrate simultaneously. By the removal of soluble monomers or oligomers and the boosted ratios of the quinone groups, the polydopamine polymers as organic redox‐active cathodes in AZBs deliver large specific capacity (372.3 mA h g −1 at 50 mA g −1 ), excellent toughness, and long‐term cyclic durability (80% retention over 1700 cycles at 1000 mA g −1 ). Moreover, the power textiles with custom‐tailored patterns can be prepared by the direct use of the fiber electrodes as the threads for a sewing and loom machine. The sewn or woven power textiles display stable electrochemical performances that can power various electronic devices under different bending conditions, even after washing for 3 h. This work provides great potential for large‐scale production of AZBs with high‐performance for next‐generation wearable energy‐storage devices. Abstract : Weavable, sewable, and washable power textiles with customized patterns are developed by using optimized quinone‐rich polydopamine as cathode materials and Zn wire anodes for aqueous zinc battery. The power textile delivers excellent electrochemical performances and flexibility, demonstrates promising large‐scale application as flexible and wearable energy storage devices.